Rodumna (Roanne, Loire), le village gaulois - Lavendhomme, Marie-Odile; Guichard, Vincent (Documents d'archéologie française, 1997)
This book provides a synthesis of the archeological research carried out in the town of Roanne (Loire) It was the site of a small Roman town whose name on the Peutinger Table and in Ptolomey is recorded as Rodumna and whose Gallic origin has been recognised since the 1950s. The small agglomeration of the late Iron Age became a maior centre of population in the Gallo roman civitas ot the SegusiaviThe work includes a detailed catalogue of the finds which can act as a basis for comparisons with other sites in central Gaul. The evolution of the settlement area from the 2nd and 1st centuries BC is described in detail. The study of the linds shows an important analysis of then evolution and the different stages of development in what was a crucial period for the history of Gaul culminating in the « romanization ». The discoveries also allow an interpretation of several aspects of daily life : the domestic architecture, diet industries, trade... Based on the material culture, these studies allow us to deal with certain aspects of the economy and to describe the material culture of theSegusiavi within the regional context.This volume is followed by another monograph in the Daf series on the Gallo-Raman occupation.